A FRET-based fluorescent and colorimetric probe for the specific detection of picric acid. Issue 55 (12th September 2018) - Zhang, Ensheng; Ju, Ping; Guo, Pu; Hou, Xiufang; Hou, Xueyan; Lv, Haiming; Wang, Ji-jiang; Zhang, Yuqi
Abstract : A FRET-based fluorescent and colorimetric chemo-sensor has been designed and synthesized for the selective and sensitive detection of picric acid. Abstract : Picric acid (PA) as an environmental pollutant and high explosive, has recently received considerable attention. In this paper, a novel fluorescent and colorimetric chemo-probe (L ) for the highly selective and sensitive detection of picric acid has been revealed. The probe was facilely constructed using rhodamine B, ethylenediamine and 4-(9 H -carbazol-9-yl)benzoyl chloride. Significant fluorescence changes based on an intramolecular fluorescence resonance energy transfer (FRET) effect followed by a distinct color change from colorless to pink were observed after addition of picric acid to the probe solution. Selectivity measurements revealed that the as-synthesized probe exhibited high selectivity toward PA in the presence or absence of other analytes. The experimental titration results suggested that the as-synthesized probe is an effective tool for detection of PA with a nanomolar scale detection limit (820 nM) and could also serve as a "naked-eye" indicator for PA detection.